Do rising returns to education justify "helicopter" parenting? - Matthias Doepke; Fabrizio Zilibotti (IZA World of Labor, 2021)
Parents now engage in much more intensive parenting styles compared to a few decades ago. Today's parents supervise their children more closely, spend more time interacting with them, help much more with homework, and place more emphasis on educational achievement. More intensive parenting has also led to more unequal parenting: highly educated parents with high incomes have increased their parenting investments the most, leading to a growing "parenting gap" in society. These trends can contribute to declining social mobility and further exacerbate rising inequality, which raises the question of how policymakers should respond.
Keywords: I24; I26; 330; parenting; parenting style; inequality; returns to education